Exploring the Knowledge of Oral Medicine Specialists towards Salivary Diagnostic Markers for Oral and Systemic Diseases - V. Divyadharsini; T.N. Uma Maheswari (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Aim: To assess the knowledge, attitude and perception of salivary diagnostic markers among Oral Medicine Specialists.Background: Early detection plays a crucial role in treatment planning and prognosis. Saliva serves as a potential diagnostic fluid as it is economic, non-invasive and gives information about oral & general health. Saliva can be used for clinical diagnosis, disease monitoring and decision making. Salivary constituent’s effective indicators of local and systemic disorders. Main problem is standardization of saliva collection methods as it is heterogeneous across studies.Materials And Methods: A 15 multiple choice questionnaire was prepared by the principal investigator and the guide circulated among peers for validation. An online survey was created using google forms and distributed among Oral Medicine Specialists. Data was tabulated in Excel spreadsheets. Imported to IBM SPSS software version 2.0 and statistical analysis were performed. Frequency, percentage and chi square test was performed.Results: Oral medicine specialists were mostly aware about recent salivary diagnostic markers. Majority of the participants believe that salivary biomarkers can serve as a diagnostic & prognostic tool. 70% of the participants feel that saliva can replace tissue or serum as a biomarker and can be translated into routine clinical practice.Conclusion: Oral medicine specialists have adequate awareness and knowledge about salivary diagnostic markers, but certain knowledge has to be brushed up among them. Majority of participants showed a positive attitude towards its use as a diagnostic & prognostic tool. Furthermore, they need to be trained on these grounds to help them treat their patients in the best possible way.